PENENTUAN TARIF PREMI PADA ASURANSI KENDARAAN DENGAN BESAR KLAIM BERDISTRIBUSI EKSPONENSIAL DAN GAMMA - Prabowo, Agung; Sulthan Izbik Riska Alfaridzi (P3M Trisakti School of Insurance (TSI), 2023)
Calculation of vehicle insurance premium rates can be done using the aggregate claims model. The aggregate claims model consists of a combination of two independent random variables, namely the number of claims that occur and the amount of claims for each event. The research method is in the form of literature studies and case studies using secondary data in the form of data on the number of claims and the amount of claims collected from January 2013 to December 2019. Based on the data collected, there were 802 claims with the smallest claim being IDR 50,000 and the largest being IDR 211,715,000. Testing the hypothesis shows that the data on the number of claims has a Poisson distribution, and the amount of claims follows two types of distribution, namely the exponential and gamma distribution so that the aggregate claim distribution is a combination of Poisson-Exponential and Poisson-Gamma. Parameter estimation for each distribution is carried out by the moment method with available secondary data. This study concludes that the use of the pure premium principle provides the same premium rate for both distributions of aggregate claims, amounting to IDR 82,856.39 per month per person. While the use of the expected value principle provides a premium rate for the Poisson-Gamma aggregate claims distribution 8.76 times greater than the Poisson- Exponential aggregate claims distribution, namely IDR 1,920,019.55 per month and IDR 219,155.20 per month, respectively.